The effectiveness of evolutionary governance in mega construction projects: a moderated mediation model of relational contract and transaction cost - Wang, Dedong; Fang, Shaoze; Fu, Hongwei (Journal of Civil Engineering and Management, 2019)
Mega construction project governance is an evolutionary process characterized by high transaction costs and complex interrelationships. Based on transaction cost theory, relational contract theory and evolutionary governance theory, this study explored the impact of evolutionary project governance on mega construction project performance by collectively considering the mediating effect of transaction costs and the moderating effect of a relational contract. Partial least squares structural equation modeling was used to test the hypotheses based on data collected from 176 respondents. The results show that evolutionary project governance would be more effective in increasing project performance and reducing transaction costs in the context of a relational contract. Reducing transaction costs is an effective way to improve project performance, and it is an important mediation variable between evolutionary project governance and project performance in the context of a relational contract. The results enrich the theory on mega construction project governance and reduce the imbalance between theory and practice in previous studies.